2015
DOI: 10.1200/jco.2013.49.4864
|View full text |Cite
|
Sign up to set email alerts
|

Deep Sequencing Identifies IDH1 R132S Mutation in Adult Medulloblastoma

Abstract: A 62-year-old woman presented with headaches in 2002. A magnetic resonance imaging scan showed a lateral right cerebellar hemisphere abnormality on fluid-attenuated inversion recovery, but no additional work-up was pursued at that time. In February 2007, she developed worsening headaches and dizziness; a repeat magnetic resonance imaging scan demonstrated an enlarged, gadoliniumenhancing mass composed of four distinct nodules (Fig 1A, arrow). Biopsy demonstrated a small round blue cell tumor, with lymphoma and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 23 publications
1
10
0
Order By: Relevance
“…glioma CpG island methylator phenotype, G-CIMP) 27,28 . We identified six IDH1 R132C mutations (five SHH, one WNT), consistent with a recent case report 29 (Extended Data Fig. 6e).…”
Section: Resultssupporting
confidence: 91%
“…glioma CpG island methylator phenotype, G-CIMP) 27,28 . We identified six IDH1 R132C mutations (five SHH, one WNT), consistent with a recent case report 29 (Extended Data Fig. 6e).…”
Section: Resultssupporting
confidence: 91%
“…The material was then sent for DNA and RNA extraction. Aliquots of nucleic acid were used for analysis on the Ion Torrent AmpliSeq Cancer panel ( Singh et al 2013 ; Snuderl et al 2014 ) and for whole genome and transcriptome analysis on the Illumina HiSeq platform as previously described.…”
Section: Introductionmentioning
confidence: 99%
“…Dysfunctional TET and/or IDH genes in uence the regulation of DNA hydroxymethylation and lead to reduction of 5hmC generation in cancers [19]. However, previous data showed that gene mutations of TET1/2/3 and IDH1/2 were extremely rare in MBs [47][48][49][50]. In this study, we found that reduced 5hmC in MBs relate to decreased expression of TET1/2 proteins, suggesting that the inactivation of TET1/2 proteins may be responsible for the altered 5hmC levels in MBs.…”
Section: Discussionmentioning
confidence: 99%